Subsidence events in the Krafla area: Preliminary report based on tilt and distance measurements - Tryggvason, Eysteinn (Nordic Volcanological Institute, University of Iceland, Reykjavik, IS, 1978)
In the inflation-deflation sequence of the Krafla magma chamber since its beginning in 1975, 10 deflation or subsidence events have been identified until July 1978. The tilt and distance measurements relating to these subsidence events are discussed in some detail. All of these subsidence events are associated with horizontal magma flow along the N-S trending fissure zone, which goes through the central part of the suggested Krafla caldera to form a dike 3 to 5 meter wide, 80 km long and 1.0 to 2.5 km high from the bottom to the top. The total volume of magma, which flowed out of the Krafla magma chamber during these 10 events, is estimated as 392 x 10{sup 6} msup 3, whereof 318 x 10{sup 6} msup 3 are estimated to have flowed northwards, 72 x 10{sup 6} msup 3 southwards and about 2 x 10{sup 6} msup 3 came to the surface as basaltic lava.